Co-creating resilient landscapes: transitioning to a multifunctional approach in India - Borah, Gulshan; Yadav, Shweta; Samaddar, A.; Kumar, Gopal; Sikka, Alok (International Water Management Institute, 2025)
The CGIAR Multifunctional Landscapes (MFL) Science Program represents a transformative approach to sustainable development, aiming to reimagine rural futures through holistic landscape management that integrates agriculture, environment, nutrition, and policy. As part of the program’s rollout in India, a national consultation titled “Co-creating Resilient Landscapes: Transitioning to a Multifunctional Approach in India” was convened on August 7, 2025 in Pune, Maharashtra, jointly organized by the International Water Management Institute (IWMI) and the Alliance of Bioversity International and CIAT. The consultation underscored that building multifunctional landscapes in India demands continuous co-creation across sectors and scales, ensuring biodiversity conservation, climate resilience, and equitable livelihoods within planetary boundaries.